2009
DOI: 10.1007/s10526-009-9238-5
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic fungi and insect behaviour: from unsuspecting hosts to targeted vectors

Abstract: The behavioural response of an insect to a fungal pathogen will have a direct effect on the efficacy of the fungus as a biological control agent. In this paper we describe two processes that have a significant effect on the interactions between insects and entomopathogenic fungi: (a) the ability of target insects to detect and avoid fungal pathogens and (b) the transmission of fungal pathogens between host insects. The behavioural interactions between insects and entomopathogenic fungi are described for a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 85 publications
1
64
0
7
Order By: Relevance
“…Una disminución en el consumo pudo ser mayor si los escarabajos evitaron alimentarse de las hojas cubiertas con esporas del hongo. Otros autores han indicado que las blastosporas y conidias de hongos entomopatógenos producen metabolitos bioactivos y enzimas degradadoras de cutícula que pueden causar una alimentación evasiva y reducida en insectos (Avery et al 2011;Meyling y Pell 2006;Quesada-Moraga et al 2006;Ali et al 2010;Baverstock et al 2010). Ali et al (2010) demostraron que los filtrados de cultivos que tenían enzimas degradadoras de cutícula de I. fumosorosea podrían ser usados potencialmente para reducir el consumo de P. xylostella.…”
Section: Resultados Y Discusiónunclassified
“…Una disminución en el consumo pudo ser mayor si los escarabajos evitaron alimentarse de las hojas cubiertas con esporas del hongo. Otros autores han indicado que las blastosporas y conidias de hongos entomopatógenos producen metabolitos bioactivos y enzimas degradadoras de cutícula que pueden causar una alimentación evasiva y reducida en insectos (Avery et al 2011;Meyling y Pell 2006;Quesada-Moraga et al 2006;Ali et al 2010;Baverstock et al 2010). Ali et al (2010) demostraron que los filtrados de cultivos que tenían enzimas degradadoras de cutícula de I. fumosorosea podrían ser usados potencialmente para reducir el consumo de P. xylostella.…”
Section: Resultados Y Discusiónunclassified
“…In contrast to the passive dispersal of infective conidia on wind currents, the dispersal of P. neoaphidis by coccinellids is targeted as the pathogen is directly transported between aphid colonies. When P. neoaphidisinfected cadavers are low in number or the habitat is diverse, targeted dispersal by coccinellids could be the most important mode of dispersal (Roy et al, 2001;Baverstock et al, 2010). However, Roy et al (2003) found that C. septempunctata inoculated with P. neoaphidis were only able to vector the pathogen within 4 h of inoculation and conidia vectored onto plants by foraging C. septempunctata were only infective up to 24 h post conidia dispersal (Roy et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…However, Roy et al (2003) found that C. septempunctata inoculated with P. neoaphidis were only able to vector the pathogen within 4 h of inoculation and conidia vectored onto plants by foraging C. septempunctata were only infective up to 24 h post conidia dispersal (Roy et al, 2003). Nonetheless, vectoring is seen as an important form of dispersal and methods of manipulating this in augmentative and conservation biocontrol strategies are being investigated (Furlong et al, 1995;Bird et al, 2004;Ekesi et al, 2005;Down et al, 2009;Baverstock et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Simple laboratory bioassays can provide a measure of insect mortality in the presence of a pathogen but experiments designed to include elements of spatial complexity are critical to improving accuracy of predictions. The papers reviewed by Baverstock et al (2009) demonstrate this and reveal manipulations of host behaviour induced by fungi and countermeasures employed by the host (Roy et al 2006). The often complex interactions between fungus and host are being unravelled through eloquent research and the importance of these often subtle behavioural modifications in determining the success or failure of biological control cannot be underplayed.…”
mentioning
confidence: 88%
“…Baverstock et al (2009) provide a review of fungal entomopathogens and insect behaviour. The behavioural response of an insect to a fungal pathogen will not only have a direct effect on the efficacy of the fungus as a biological control agent but also provide us with a model system for understanding interactions within guilds.…”
mentioning
confidence: 99%